2023
DOI: 10.1186/s12877-023-03911-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between sarcopenia and mild cognitive impairment in the older Korean population

Abstract: Background A link between sarcopenia and cognitive function has been proposed and is supported by several investigations. Nevertheless, the sex-linked relationship between these two diseases has been scarcely investigated. This cross-sectional study investigated sex differences in the association between sarcopenia and mild cognitive impairment. Methods We included all 286 participants aged 60 years or older with MCI who visited the Department of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a cohort study that followed a large population over a relatively long period of time, the relationship between HGS and dementia risk, cognition, and neuroimaging was confirmed, and similar results were found in men and women [ 31 ]. Conversely, there is a previous study that found differences in the relationship between sarcopenia and MCI depending on sex [ 35 ]. In this study, the relationship between sarcopenia and MCI according to sex was due to sex hormones such as androgen and estrogen [ 35 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a cohort study that followed a large population over a relatively long period of time, the relationship between HGS and dementia risk, cognition, and neuroimaging was confirmed, and similar results were found in men and women [ 31 ]. Conversely, there is a previous study that found differences in the relationship between sarcopenia and MCI depending on sex [ 35 ]. In this study, the relationship between sarcopenia and MCI according to sex was due to sex hormones such as androgen and estrogen [ 35 ].…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, there is a previous study that found differences in the relationship between sarcopenia and MCI depending on sex [ 35 ]. In this study, the relationship between sarcopenia and MCI according to sex was due to sex hormones such as androgen and estrogen [ 35 ]. In other words, there is a difference in the distribution of sex hormone receptors that affect muscle mass in the hippocampus between men and women [ 36 ].…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, the stratified results revealed that the association was not statistically significant in males and those with higher education, which may potentially explain the marginal significance in the main analysis. Recent research on 286 older adults in South Korea has also highlighted sex differences, with sarcopenia exhibiting a significant association with cognitive impairment in older females but not in males [ 55 ]. These distinctions may be attributed to variances in gender-specific physiology [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on 286 older adults in South Korea has also highlighted sex differences, with sarcopenia exhibiting a significant association with cognitive impairment in older females but not in males [ 55 ]. These distinctions may be attributed to variances in gender-specific physiology [ 55 ]. Furthermore, participants with a higher level of education who had sarcopenia may have been more inclined to seek medical attention and receive care, potentially contributing to this marginal significance.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses collected participants' data on socio-demographic information, lifestyle, and personal factors. The clinical staff diagnosed CIND, referring to all available data from clinical examinations and neuropsychological evaluations [28]. Individuals with CIND are defined as those without dementia and with cognitive impairment.…”
Section: Study Populationmentioning
confidence: 99%